1985
DOI: 10.1007/bf00120834
|View full text |Cite
|
Sign up to set email alerts
|

International turbulence comparison experiment (ITCE-81)

Abstract: The main results of the International Turbulence Comparison Experiment (Tsimlyansk, U.S.S.R., June-July 1981) are presented. Groups from G.D.R., Poland, U.S.S.R., and Czechoslovakia took part in the experiment, while Bulgarian researchers were present as observers. A comparison of in situ measurements (by acoustic anemometers, thermoanemometers, and resistance thermometers) among themselves and with remote soundings (by sodars) was made. Simultaneous measurements of turbulent fluctuation characteristics and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 16 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…In 1975 and1976 I was a member of the KASPEX-75 and KASPEX-76 expeditions with the Institute of Oceanology, Moscow (director: A. S. Monin) and in 1981 I participated in the International Turbulence Comparison Experiment in Tsimlyansk, Russia (Tsvang et al, 1985) with the Institute of Physics of the Atmosphere (director: A. M. Obukhov).…”
Section: Introductionmentioning
confidence: 99%
“…In 1975 and1976 I was a member of the KASPEX-75 and KASPEX-76 expeditions with the Institute of Oceanology, Moscow (director: A. S. Monin) and in 1981 I participated in the International Turbulence Comparison Experiment in Tsimlyansk, Russia (Tsvang et al, 1985) with the Institute of Physics of the Atmosphere (director: A. M. Obukhov).…”
Section: Introductionmentioning
confidence: 99%
“…The first experiment was carried out in 1968 near Vancouver, Canada, over the ocean (Miyake et al 1971), followed by one over steppe country at Tsimlyansk, Russia in 1970 (Tsvang et al 1973). Additional experiments were carried out in 1976 in Conargo, Australia (Dyer 1981;Dyer et al 1982) and in 1981 again in Tsimlyansk (Tsvang et al 1985). In these early intercomparison experiments mostly prototype instrumentation was tested.…”
Section: Introductionmentioning
confidence: 99%
“…As to the magnitude of the exponent in (lo), a number of experimenters have pointed out that dimensional considerations suggest that +,, should become proportional to (-z/L)-"~ as conditions approach free convection (e.g., Carl et al, 1973;Troen and Mahrt, 1986). Measurements by Tsvang et al (1985) were shown to fit a -l/3 power relation over the range -0.70 < zlL < -0.03.…”
Section: Introductionmentioning
confidence: 99%